Mix of destinations and sedentary behavior among Brazilian adults: a cross-sectional study - Alex Antonio Florindo; Gavin Turrell; Leandro Martin Totaro Garcia; João Paulo dos Anjos Souza Barbosa; Michele Santos Cruz; Marcelo Antunes Failla; Breno Souza de Aguiar; Ligia Vizeu Barrozo; Moises Goldbaum (BMC, 2021)
Abstract Background Sedentary behavior is influenced by contextual, social, and individual factors, including the built environment. However, associations between the built environment and sitting time have not been extensively investigated in countries with economies in transition such as Brazil. The objective of this study is to examine the relationship between sitting-time and access to a mix of destinations for adults from Sao Paulo city, Brazil. Methods This study uses data from the Health Survey of Sao Paulo. Sedentary behavior was assessed by a questionnaire using two questions: total sitting time in minutes on a usual weekday; and on a usual weekend day. The mix of destinations was measured by summing the number of facilities (comprising bus stops, train/subway stations, parks, squares, public recreation centres, bike paths, primary health care units, supermarkets, food stores, bakeries, and coffee-shops) within 500 m of each participant's residence. Minutes of sitting time in a typical weekday and weekend day were the outcomes and the mix of destinations score in 500 m buffers was the exposure variable. Associations between the mix of destinations and sitting time were examined using multilevel linear regression: these models accounted for clustering within census tracts and households and adjusted for environmental, sociodemographic, and health-related factors. Results After adjustment for covariates, the mix of destinations was inversely associated with minutes of sitting time on a weekday (β=− 8.8, p=0.001) and weekend day (β=− 6.1, p=0.022). People who lived in areas with a greater mix of destinations had shorter average sitting times. Conclusion Greater mix of destinations within 500 m of peoples' residences was inversely associated with sitting time on a typical weekday and weekend day. In Latin American cities like Sao Paulo built environments more favorable for walking may contribute to reducing sedentary behavior and prevent associated chronic disease.